Hitler Lives - Siegel, Don (United States, 1945)
The re-edited version of the film “Your Job in Germany”, “Hitler Lives” was produced at the end of WWII and warned that although Adolf Hitler was dead, his ideas lived on in the German people. The world must stay ever vigilant, so that Germany cannot wage war against the world again. A propaganda film warning American soldiers that they also have to be on guard against those in America who sympathized with Germany and preach race hatred and violence in the country.
Keywords: United States